Development of Archives Management Information System with RFID and SMS Gateway - Habib, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Filing is something that can not be exemplified by an organization or institution, which has a lot of important information, can be used to determine or influence concrete something that goes on within the institution or organization, in its development, the archive that remains, the technology today. not only the objects that can be touched but also something that is digitally we can call with digital archives or electronic archives (E-Archives). Archive management is an attempt by archives to present services that match the character of today's society. Through this report, the author wants to know how the security and security of the system in the E-Archive with RFID and SMS Gateway to anticipate the loss of archival data, as well as devices that become a medium for storing modern information to facilitate the task and archive services forward. Using this additional RFID (Radio Frequency Identification) tool is expected to confuse users and users in identifying users and documents archived in the E-Archive system. And the process of disclosure of documents that have been identified, and minimize the provision of loss of documents due to filing officer misconduct. Here also I added SMS Gateway as a reminder (Reminder) that is suitable to forget Archive documents to the archive officers not to be lost.